Wizerunek konia terapeuty w filmie na wybranych przykładach - Lusińska, Anna (Zoophilologica. Polish Journal of Animal Studies, 2020)
The image, in general, is understood as an image, an image or a likeness. Nowadays, this concept is associated with its shaping and reception in order to influence the environment. Thinking about the image, first of all, its personal connotations are taken. Can you therefore analyze the image of an animal, and more specifically a horse? It turns out that yes, because this representative of the even-toed ungulate, accompanying man in his life since prehistory, appeared in art, including film. He was honored to be his object or rather subject. Among the many roles he had to play, there was also a humanizing role – the therapist. The aim of the article was to show the image of the horse as a therapist in selected film examples and its analysis.